2012
DOI: 10.1039/c2an35821b
|View full text |Cite
|
Sign up to set email alerts
|

Post-collection processing of Schirmer strip-collected human tear fluid impacts protein content

Abstract: We examine the impact of post-collection sample handling on the protein composition of human tear samples. In particular, we characterize diffusion-based protein extraction from Schirmer strips. These strips of filter paper membrane are the de facto standard for tear fluid collection and storage, with diffusion-based protein elution off the strip being the most widely reported protein extraction strategy. Nevertheless, the diffusion-based protein elution strategy remains uncharacterized regarding downstream fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 55 publications
0
50
0
1
Order By: Relevance
“…It has been shown that 3-h extraction is sufficient to achieve time-independent protein extraction from Schirmer strips [148,149,154]. In our study, we experienced a slight increase in the number of identified proteins with overnight extraction compared with a 4-h extraction.…”
Section: The Choice Of Extraction Volume Time and Temperaturementioning
confidence: 50%
“…It has been shown that 3-h extraction is sufficient to achieve time-independent protein extraction from Schirmer strips [148,149,154]. In our study, we experienced a slight increase in the number of identified proteins with overnight extraction compared with a 4-h extraction.…”
Section: The Choice Of Extraction Volume Time and Temperaturementioning
confidence: 50%
“…41 cellulose filter paper and possess specific characteristics to promote tolerance (5-mm width × 35-mm length, 0.22-mm thick, 20-25 µm porosity, foldable extremity for ease of insertion). 249,257 In addition to their conventional use for aqueous tear assessment, Schirmer strips can retrieve tear fluid for bioanalytical purposes in humans, 182,216,219,220,228,231,258 dogs, 190,209,211,214,215,240,259 and small laboratory species. 244,260,261 For instance, Schirmer strips were used for indepth characterization of proteomics in human 173 and canine tears, 190 and can also successfully recover specific analytes such as cytokines, 200,258 clusterin, 182 and xenobiotics.…”
Section: Indirect Tear Samplingmentioning
confidence: 99%
“…250 On this note, the main limitation of indirect sampling is the "invasiveness" of the technique, at risk of promoting reflex tearing and altering the composition of the tear fluid; indeed, several studies showed variable tear composition between directly and indirectly collected samples, with notable differences in the qualitative and quantitative profiles obtained for tear lipids 221 and tear proteins. 216,220,226,269 Another important drawback is related to the adsorptive properties of Schirmer strips or absorbent sponges, that is, incomplete release of tear compounds following extraction 209,214,257,258,265 ; however, the authors believe this limitation can be minimized/controlled with adequate precautions (see Section 3.3).…”
Section: Indirect Tear Samplingmentioning
confidence: 99%
“…The Schirmer test is widely used to measure tear volume in multicenter clinical trials because it is easy to apply and does not require special equipment 14,15. This test can also be used to collect tear samples16 for analysis of cytokines,17 nucleic acids,18 and immunoglobulin 19…”
Section: Discussionmentioning
confidence: 99%